Ten new insights in climate science 2022. (10th November 2022) - Martin, Maria A.; Boakye, Emmanuel A.; Boyd, Emily; Broadgate, Wendy; Bustamante, Mercedes; Canadell, Josep G.; Carr, Edward R.; Chu, Eric K.; Cleugh, Helen; Csevár, Szilvia; Daoudy, Marwa; de Bremond, Ariane; et al.
Abstract : Non-technical summary: We summarize what we assess as the past year's most important findings within climate change research: limits to adaptation, vulnerability hotspots, new threats coming from the climate–health nexus, climate (im)mobility and security, sustainable practices for land use and finance, losses and damages, inclusive societal climate decisions and ways to overcome structural barriers to accelerate mitigation and limit global warming to below 2°C. Technical summary: We synthesize 10 topics within climate research where there have been significant advances or emerging scientific consensus since January 2021. The selection of these insights was based on input from an international open call with broad disciplinary scope. Findings concern: (1) new aspects of soft and hard limits to adaptation; (2) the emergence of regional vulnerability hotspots from climate impacts and human vulnerability; (3) new threats on the climate–health horizon – some involving plants and animals; (4) climate (im)mobility and the need for anticipatory action; (5) security and climate; (6) sustainable land management as a prerequisite to land-based solutions; (7) sustainable finance practices in the private sector and the need for political guidance; (8) the urgent planetary imperative for addressing losses and damages; (9) inclusive societal choices for climate-resilient development and (10) how to overcome barriers to accelerate mitigation and limit global warming to below 2°C. Social media summary: Science has evidence on barriers to mitigation and how to overcome them to avoid limits to adaptation across multiple fields.